To solve the quadratic equation \((x + 36)^2 - 38 = 251\) using square roots, follow these steps:
-
Isolate the squared term: \[ (x + 36)^2 - 38 = 251 \] Add 38 to both sides: \[ (x + 36)^2 = 251 + 38 \] \[ (x + 36)^2 = 289 \]
-
Take the square root of both sides: \[ x + 36 = \pm \sqrt{289} \]
Since \(\sqrt{289} = 17\): \[ x + 36 = 17 \quad \text{or} \quad x + 36 = -17 \]
-
Solve for \(x\) in both cases:
-
For \(x + 36 = 17\): \[ x = 17 - 36 \] \[ x = -19 \]
-
For \(x + 36 = -17\): \[ x = -17 - 36 \] \[ x = -53 \]
-
-
The solutions are: \[ x = -19 \quad \text{and} \quad x = -53 \]
Therefore, the solution set is \({ -19, -53 }\).
The correct response is: \[ { -19, -53 } \]